OPTIMALISASI MEDIA SOSIAL FACEBOOK UNTUK MENDUKUNG PERLUASAN JARINGAN PEMASARAN BAGI KELOMPOK WANITA KREATIF (KWK) SEROJA - Retnowati Retnowati; Eko Nur Wahyudi; Sariyun Naja Anwar; Hersatoto Listiyono (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
The Creative Women Group namely KWK Seroja, which consists of housewives, has great potential to increase product marketing networks, because the business it has been in has been in business for almost 10 years with a relatively productive age. Until now KWK Seroja members have businesses in the fields of convection, food, rental and souvenirs, but still use traditional marketing models such as opening a business at home or marketing it door-to-door. The rapid use of social media such as Facebook can help marketing more efficiently and effectively, due to the extensive network. KWK Seroja needs to be helped through information about the importance of marketing transformation from traditional to social media bases, namely optimized Facebook fans page. KWK Seroja also needs assistance to participate in the UMKM exhibition to strengthen its position in the eyes of the community. The results obtained were good enthusiasm from the members who were able to create a fan page in accordance with their respective products and a willingness to follow the UMKM exhibition once a year.